Achievements and Requirements of Teachers' Guild-Political Activism (2010s) - Heidar Shahriari; ehsan balaghi inanloo (رهیافتهای سیاسی و بین المللی)
Extended abstractIntroduction and Purpose: The teachers' guild-political activism in the 2010s is not only considered as a new phase in the history of their guild-political activism, it has also various aspects and traits such as non-violence, high participation, inclusiveness and continuity which significantly distinguished it from their past activism and even that of other social groups. The main purpose of this research is to assess the achievements of teachers' guild-political activism in the 2010s and the requirements of their activism. Although their requirements and their achievements are different aspects of their guild-political activism, these aspects are correlated: the former (requirements) advances the latter (achievements). Method:  Since this research deals with two separate but interrelated questions (i.e. it assumes that the requirements are the foundation of achievements) and it also assesses the achievements through quantitative method and the requirements through qualitative method, thereby, the data analysis method is a mixed method: multi-level mixed method. The achievement data was collected through semi-open interviews (8 closed questions and 8 open questions) with 30 teachers' guild-political activists, and then the average of all interviewees' responses (based on the Likert scale) in each item has been analyzed. The requirement data has also been collected through library and qualitative method, and finally, by placing all the data together, a final analysis has been concluded.Findings: The findings of the research indicate that among the eight significant professional-political achievements of teachers (both in-guild and out-guild), the most important achievements, in order, are the approval of the teacher ranking plan, the strengthening of solidarity and cohesion, the importance of the existence of the profession and its associated structures, and setting an example for other organizations. Their most important requirements have been, also, strategic unity, promotion of the civil-legal trainings of their activism, the continuity of their guild membership process, making the educational system accountable and education policies more efficient. Among 8 items of their guild-political achievements, the approval of rating plan with 4.16% is the highest average and the improvement of living conditions is the lowest average with 1.3%. In total, the guild achievements with 70.3% frequency are more important than non-guild achievements with 3.47%. The requirements of teachers' activism, which advance their achievements are as follow: following one strategic unity, promotion of the civil-legal trainings of their activism, the continuity of their guild membership process, making the educational system accountable and education policies more efficient (meritocracy, decreasing the leadership level of government, improving the social dignity of teachers through governance discourse, paying attention to their livelihood policies, paying attention to educational demands, redefining the professional identity of teachers) and recognizing their guild.Conclusion: The achievements or successes of teachers' activism, both in the past and in the future, are dependent on requirements such as making educational policies more efficient through the promotion of some parameters such as meritocracy, decreasing the leadership level of government, improving the social dignity of teachers, paying attention to their livelihood policies, paying attention to educational demands etc., on one hand, and recognizing their associations by political system. Although this research has some deficiencies, it can be a step for future researches regarding other dimensions of teachers' activism, educational issues, socio-cultural development issues and the future researches of various social movements and other guild movements; thereby, this research can lead to a favorable scientific and practical result for better policies through a thematic and methodical survey.